Effects of a Warm up Program Consisted of Dynamic Stretch, Strength and Plyometric and Exercises (DSP) on Physical Health of Young Male Soccer Players with Prevention of Knee and Ankle Injuries Approach - Seyed mojtaba Asgari; Shahnaz shahrbanian (Iranian Association of Health Education and Health Promotion, 2018)
Background and Objective: Maintaining football players' good physical health status is a key element in a successful soccer competition. Knee and ankle joints have shown the highest rate of injuries. Frequent injuries in such joints will result in increasing of risk of osteoarthritis, shortness in the injured limb in comparison to symmetry limb and financial problems due to the cost paid for the treatment. The purpose of this study was to investigate the effect of a specific warm up program consisting of dynamic stretch, strength and plyometric exercises (DSP) on prevention of knee and ankle injuries among young male soccer players.  Methods: Two teams of Iranian young soccer league (2017-2018) who accepted to join the study were randomly divided into the experimental (N=25) and control (N=29) groups. During the study period, the experimental group performed the DSP program 3 times per week for warming up before training and competition. Control group continued its routines warm up program. Having confirmed by a physician, injuries occurred during the season were recorded in the injury registration form. Chi- square analysis test was used to compare the injuries between two groups.  Results: Results indicated a significant difference in knee injuries between two groups as players in experimental group were injured less than control group (P=0.029); while there was no significant difference between two groups in ankle injuries (P=0.518).  Conclusion: This study confirmed that using a systematic warm up program including plyometric exercises plus strengthening of muscles involved in the movement of knee and ankle joints results in the prevention of knee and ankle injuries.